The Effect of Forensic Audit on the Speed and Accuracy of Financial Case Resolution by Taking Case Complexity, Expertise Auditors, and Supporting Technology - Doloksaribu, Kristin Natalia; Tampubolon, Tesalonika; Putra, M Syukrillah; Dwilita, Handriyani (Educational Studies and Research Journal, 2025)
Forensic audits can speed up the resolution of financial cases by providing faster and more precise analysis. Forensic AUDITS increase the accuracy of case resolution by providing a more thorough investigation, and clearer and more accountable evidence. The more complex a financial case, the more likely it is that the speed of case resolution will be affected. The more complex a case, the higher the likelihood of errors in the interpretation of evidence or data, which can reduce accuracy. Auditor expertise plays a very important role in speeding up the resolution of financial cases. Auditor expertise plays a key role in improving the accuracy of case resolution. Supporting technology accelerates the resolution of financial cases by increasing efficiency in data collection, analysis, fraud detection, reporting, and communication. Supporting technology plays a very large role in increasing the accuracy of case resolution.